National code of police targeting children and adolescents with hearing functional diversity (Revista cientifica In Vestigium Ire, 2020)
In order to improve coexistence and citizen security, the dissemination of the National Police Code becomes a challenge that the police institution must develop with the various populations of the country, however, and despite the efforts made, it is not yet achieves an effective generality of communication throughout the national territory, in this sense there are other populations that are outside the contents of the National Police Code, in this case those with functional hearing diversity regardless of the medical origin of his condition.In view in understanding, making visibility and proposing in the learning context of this population, a data survey or mapping was carried out that allowed to establish learning opportunities in terms of language unification and use of technology in people with this condition. Therefore, scientific and technological support was sought in the consolidation of a didactic and innovative instrument to communicate issues of the National Police Code for appropriate use in all types of people with or without knowledge in sign language and fingerprint in particular aimed at children and adolescents.
Keywords: Service; Citizen; Citizen Security; State; National Police Code; Hearing Functional Diversity; Education